Cemento-ossifying fibroma with mandibular fracture. Case report in a young patient - Ong, A.H.M.; Siar, C.H. (1998)
The cemento-ossifying fibroma is classified as an osteogenic neoplasm of the jaws. It commonly presents as a progressively growing lesion that can attain an enormous size with resultant deformity if left untreated. A case of a large cemento-ossifying fibroma involving the left mandible is described in a 15 year old male patient. The clinical, radiographic and histological features as well as surgical findings are presented. The treatment of choice of this lesion is also emphasized. Two years after surgery, there was no evidence of recurrence and the transosseous wire used to immobilize the fracture was found to be completely buried in the jaw bone.